Alternatives for the Better Use of Electricity in Costa Rica - Castro, René (2009)
The proposal examines that, in the face of a growing demand for electric energy, Costa Rica takes advantage of the great potential available and renewable sources themselves, instead of investing in thermal power plants that work with imported resources and pollutants. In addition to this, the constraints that prevents taking advantage of this opportunity are also examined. Finally, it presents an example of an alternative for more efficient use of electricity supply by implementing a pilot plan to replace part of the fleet of electric cars, which would not only open new electricity markets, but would also help to reduce fossil fuel use in the industry with the highest consumption: Transport.